PRIMARY SCHOOL AND SECONDARY SCHOOL STUDENT’S PERCEPTIONS OF THEIR GAMES - İhsan ÜNLÜ and Alper KAŞKAYA (International Journal of Eurasia Social Sciences, 2018)
One of the biggest problems of the educators who carry games to classrooms is not being able to evaluate games in the viewpoints of children. The issue of whether children see games as a tool or as a purpose may contribute to the use of games in educational environments. Is a game an activity or a means for socializing for a child? Is it an individual activity or a group activity? Is it a free time activity or does that mean being active? The answers to these questions that will be given by children will enable us to explain games in a detailed manner in hypothetical terms and organize more planned activities for using games in educational environments. On this context, the purpose of the present study is to examine the perceptions of primary school 4th grade and secondary school 5-6th grade children towards their games. The study was conducted with 231 students studying at primary and secondary schools located in the city center of Erzincan. During the course of the study, the “Children’s Perceptions of Their Play Scale (CPTP)” was employed. The scale was developed by Barnett (2013) and was adopted by the authors of the study. It may be claimed that games are considered as being social and dealing with something by the students studying at the 4th grades of primary schools and 5-6th grades of secondary schools, who participated in the study. Among the reasons stated by the students for playing games was “To Entertain” in the first place; and “I play games to learn” ranked the last. The meaning of a game activity is “Active Play” for children who stated that they played games “To Learn Something”. Among the results of the study, they stated that they did not like being passive during their learning processes. It was also determined in the study that students prefer playing games in groups more, these preferences of theirs change according to the grade variable, and the majority of children cannot decide on their games and on what to play.